DEMOCRATIC POLITICAL REGIME: ESSENCES AND ASPECTS - MAKHMUDOV KOMAL SAMADOVICH (Scholar Express Journals, 2024)
In this article, the democratic regime, political regime, problems of political power, the role of democratic principles in the formation of state power and management, relations related to their implementation in practice, problems with the knowledge and practice of the rights and freedoms of voters, citizens, the essence of actions, organizations, institutions of democratic power specific roles and tasks are explained
Keywords: Democracy; political regime; political system